Reference jitter values for the sternocleidomastoid muscle with concentric needle electrodes. Issue 1 (2nd November 2020) - Kula, Ezgi; Tanridag, Tulin; Kahraman Koytak, Pinar; Uluc, Kayihan
Abstract: Background: The aim of this study was to establish reference jitter values for the voluntary activated sternocleidomastoid (SCM) muscle using a concentric needle electrode (CNE). Methods: The study included 39 healthy participants (20 female and 19 male) aged 18–77 y. Jitter was expressed as the mean consecutive difference (MCD) of 80–100 consecutive discharges. Filters were set at 1 and 10 kHz. The mean MCDs for all participants were pooled, and the mean value +2.5 SD was accepted as the upper limit for the mean MCD. The upper limit for individual MCD was calculated using +2.5 SD of the upper 10th percentile MCD for individual participants. Results: Mean age of the participants was 45 ± 14.5 y. Mean MCD was 16.20 ± 2.23 μs (range: 12–21 μs), and the upper limit of normal for mean MCD was 21.8 μs. The mean value for 823 individual jitters was 23.3 ± 4.61 μs (range: 6.6–36.9 μs), and the upper limit of normal for each individual jitter was 34.6 μs. Conclusions: The present findings indicate that upper normal limit for mean MCD is 22 μs and for individual data it is 35 μs.